Socio‐demographic and familial factors associated with hospital admissions and repeat admission for dental caries in early childhood: A population‐based study. Issue 6 (27th November 2021) - Chen, Rebecca; Schneuer, Francisco J; Irving, Michelle J; Chow, Clara K; Kumar, Harleen; Tsai, Carrie; Sohn, Woosung; Spallek, Heiko; Bell, Jane; Nassar, Natasha
Abstract: Objectives: Dental caries remains a complex childhood condition often requiring preventable hospital admissions. There are limited population‐based epidemiological studies that use large and linked data sets to quantify the clinical, socio‐demographic and familial risk factors related to hospital admissions for dental caries. The aim of this study was to describe and quantify the rates, socio‐demographic, clinical characteristics and familial factors including repeat admissions associated with young children admitted to hospital for dental caries. Methods: This cohort study ( n = 33, 438) used longitudinally linked hospital admission data among all children aged <six years in NSW, Australia. Socio‐demographic and admission characteristics of children and those with one versus two or more admissions for dental caries were compared. Familial risk factors were analysed for a restricted cohort of families with two or more children ( n = 18, 174) using multivariable logistic regression to assess the familial factors associated with multiple hospital admissions for dental caries adjusting for other socio‐demographic characteristics. Results: There were 33, 438 children aged <six years who had 34, 446 hospital admissions for dental caries between 2001 and 2014. The annual rate of 4.3 per 1000 children remained unchanged over the period. Most admissions required general anaesthesia (96%), and 8.4% of children had repeat admissions. Children living in disadvantaged or in regional and rural areas attending public hospitals were more likely to have dental extractions during the admission. Children from the same family had a 2.7‐fold increased odds of admission if the first child admitted was less than three years of age (adjusted odd ratio 2.69; 95% CI: 2.36–3.07), a 1.5 fold increase for socioeconomic disadvantage (aOR 1.45; 1.19 – 1.77) and a 1.9 fold increase of admission if the family had 4 or more children (aOR1.88; 1.47 – 2.42). Conclusions: Findings highlight socio‐demographic inequities associated with hospital admission for dental caries. The provision of targeted dental care programs for 'at‐risk' families should address these inequalities and presents an opportunity to reduce dental caries related hospitalizations.